An assessment of perceptions of justice in Rohingya refugees to identify mental health and psychosocial services needs and inform programme development in Bangladesh: a qualitative survey. Issue 1 (April 2020) - Fischer, Lauren; Zigman, Julia; Chowdhury, Hasan; Bazle, Razee; Islam, Mohammed; Hughes, Jordan; George, Madaline; Price, Rumi; Shidhaye, Rahul; James, Aimee; Patel, Rupa
Abstract: Background: Local non-governmental organisations (NGOs) provide mental health and psychosocial services (MHPSS) to over 1 million Rohingya refugees in Bangladesh. To provide insights to inform the development of MHPSS services in populations targeted in ethnic cleansing campaigns, we undertook a project that aimed to identify how refugees' understanding of the justice process is linked to their psychosocial wellbeing. Methods: We conducted two focus groups and 13 in-depth qualitative interviews with Rohingya refugees residing in camps in Bangladesh. Refugees were recruited from the MHPSS work area of a local NGO—Friends in Village Development, Bangladesh—where a new intensive care programme for people who have experienced sexual and physical violence in Myanmar is being developed. We used baseline intake data to select participants who were known to be from a Myanmar village that suffered violence and who had a potential need for intensive psychological therapy because of direct exposure to violence. A brief interview guide included questions about refugees' understanding of the general concept of justice, of the justice process as applied to their situation, and of the emotional impact caused by justice being realised or denied. Interviews were recorded, transcribed, and translated. Two coders analysed transcripts for key themes based on a codebook using grounded theory. Findings: Between Nov 1, 2018, and Aug 30, 2019, we interviewed ten male participants and 12 female participants aged between 10 years and 60 years. All had either experienced or witnessed violence when their villages were attacked. Respondents' concepts of justice included: a descriptive account of conflict resolution processes, noted to be culturally variable and often corrupt; and an aspirational account of full restoration of rights within their homeland. Some mentioned retributive punishment, but it was not emphasised. Participants acknowledged distress when thinking about a lack of justice, as well as a possibility of inner peace through achieving justice, but noted that even full restoration of their rights could not completely resolve the effects of the violence. Refugees reported inconsistent access to updates about repatriation, and media outlets, such as international news websites and social media sites, were not routinely accessible. Interpretation: MHPSS programmes can potentially enhance refugee wellbeing by providing education, access to news updates, and advocacy surrounding the justice process. A further understanding of how concepts of justice may inform MHPSS programming is important to improve refugee care worldwide. Funding: The Institute for Public Health, Washington University in St Louis, MO, USA and Washington University in St Louis Division of Infectious Diseases, School of Medicine, MO, USA.